Downstream bypass efficiency of Atlantic salmon Salmo salar smolts in relation to bypass cobble substrate and flow velocity - Naslund, Joacim; Bowes, Rachel E.; Greenberg, Larry; Bergman, Eva (Ecological Engineering, 2022)
River connectivity is a major environmental factor affecting fish migration through river systems. Anthropogenic barriers cause substantial delays and mortality to long-migrating diadromous fish, such as salmonids. Downstream bypasses have received little attention over the years and can be constructed in several ways, with bypass acceptance by fish shown to be problematic in many cases. This experiment investigated whether the addition of cobble in the passageway of a surface bypass could facilitate downstream movement of Atlantic salmon (Salmo salar) smolts. The experiment also determined if the addition of cobble substrate functioned similarly under five varying flow velocities, as this can directly interact with bypass design and impact bypass acceptance. Surface bypasses were constructed in large experimental flumes, into which the smolts were released and monitored for bypass passage using PIT-telemetry through 3-h night-trials. Behavior was scored using two continuously recording video cameras at the bypass construction. No clear positive effects on passage efficiency could be detected from the addition of cobble substrate in the passageway of the bypass. Based on these results, the addition of cobble substrate in a surface bypass passageway cannot be recommended as a measure to facilitate the downstream passage performance of Atlantic salmon smolts through surface bypasses. With respect to flow velocity, higher velocities within the tested range (0.48-0.75 m.s(-1)) led to faster passage.